2018
DOI: 10.1016/j.neurobiolaging.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Alzheimer's disease with brain imaging and genetic data using a neural network framework

Abstract: A long-standing question is how to best use brain morphometric and genetic data to distinguish AD patients from cognitively normal (CN) subjects and to predict those who will progress from mild cognitive impairment (MCI) to AD. Here we use a neural network (NN) framework on both magnetic resonance imaging-derived quantitative structural brain measures and genetic data to address this question. We tested the effectiveness of NN models in classifying and predicting AD. We further performed a novel analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…Multimodal neuroimaging data can provide complementary information and theoretically improve the accuracy of classification results. In order to systematically understand the formation mechanism of AD, multiscale, multimode, and heterogeneous data should be fused to mine the interaction between cross-omics variables [ 21 , 22 ]. Some methods of data fusion based on ensemble classifier, dimension-based, and multicore learning have been proposed to establish a fusion predictor for other complex diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal neuroimaging data can provide complementary information and theoretically improve the accuracy of classification results. In order to systematically understand the formation mechanism of AD, multiscale, multimode, and heterogeneous data should be fused to mine the interaction between cross-omics variables [ 21 , 22 ]. Some methods of data fusion based on ensemble classifier, dimension-based, and multicore learning have been proposed to establish a fusion predictor for other complex diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the functional connectivity features of the regions of interest also predicted the severity of the neuropsychiatric symptoms, as well as the AD pathology (indexed by baseline and change of Aβ/phosphorylated tau ratio) with above 70% accuracy rate. Furthermore, measures of MRI at baseline (GM volumes of specific regions of interest, including the hippocampus) in combination with genetic [apolipoprotein E (APOE) ε4 allele and 19 single nucleotide polymorphisms (SNPs) significantly associated with AD] 35 or hypometabolism (qualitatively investigated with 18F-fluoro-2-deoxyglucose positron emission tomography – FDG-PET) 36 information could predict the progression to AD in MCI cases clinically followed up for 24 months, reaching accuracies higher than 80%.…”
Section: Resultsmentioning
confidence: 99%
“…Using different classification approaches, several studies demonstrated that brain structural MRI (particularly the medial temporal lobe), amyloid and FDG-PET, and genetic features (in particular the APOEε4 allele) better than other imaging and genetic features predicted the distinction between AD and healthy controls and the conversion from MCI to AD. 35 , 36 , 37 , 96 …”
Section: Resultsmentioning
confidence: 99%
“…Single nucleotide polymorphism (SNP) can be used as features for classification. Ning et al reported the ability of AD risk loci in AD/NC classification [24]. Rodrí guez et al [25] selected 8 known AD-related loci and found there was no good discrimination for the classification of MCI.…”
Section: Introductionmentioning
confidence: 99%